2010
DOI: 10.1002/cmmi.384
|View full text |Cite
|
Sign up to set email alerts
|

Imaging monocytes with iron oxide nanoparticles targeted towards the monocyte integrin MAC‐1 (CD11b/CD18) does not result in improved atherosclerotic plaque detection by in vivo MRI

Abstract: Imaging of macrophages with superparamagnetic iron oxide particles (SPIO) has been performed to improve detection of atherosclerotic plaque inflammation in human and mouse studies by molecular magnetic resonance imaging (MRI). Since affinity of the monocyte/macrophage integrin MAC-1 (CD11b/CD18) is upregulated in inflammation, we generated a contrast agent targeting CD11b (CD11b-SPIOs) for improved macrophage detection in plaques. CD11b-SPIOs and non-targeted SPIOs (control-SPIOs) were incubated in vitro with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Iron oxides have been successfully applied for the MR visualization of macrophages in cardiovascular diseases [15-17]. Nevertheless, targeting of iron oxides to CD11b/CD18, which is expressed on macrophages, did not improve specificity for MR imaging of macrophages in a mouse model of atherosclerosis [18]. Recently, Gd-labeled liposomes were used to visualize monocytes and/or macrophages infiltration in the mouse myocardium up to 7 days after myocardial infarction [19].…”
Section: Discussionmentioning
confidence: 99%
“…Iron oxides have been successfully applied for the MR visualization of macrophages in cardiovascular diseases [15-17]. Nevertheless, targeting of iron oxides to CD11b/CD18, which is expressed on macrophages, did not improve specificity for MR imaging of macrophages in a mouse model of atherosclerosis [18]. Recently, Gd-labeled liposomes were used to visualize monocytes and/or macrophages infiltration in the mouse myocardium up to 7 days after myocardial infarction [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Von Zur Mohlen et al [92] CD11b-SPIOs and non-targeted SPIOs (controlSPIOs) were incubated in vitro with human monocytes/macrophages. As quantified by SPIO-induced MRI signal extinction, intracellular iron-content was significantly higher in monoytes/ macrophages incubated with CD11b-SPIO than with control-SPIO in vitro (p < 0.05), suggesting an improved uptake of CD11b-SPIOs into monocytes.…”
Section: Role Of Monocytesmentioning
confidence: 99%
“…Thus, it serves as an effective cellular system for innate immune response evaluation. Recent reports mainly focused on labeling monocyte cells with NPs for therapeutic imaging (Settles, et al, 2011;Von zur Muhlen et al, 2010;Wu et al, 2006), and only a few reports demonstrated the proinflammatory effects of iron oxide NPs on human monocyte cell lines (Laskar et al, 2012;Zhu et al, 2011). Further understanding of the interactions between NPs and human monocyte cell line will be beneficial for predicting NP-induced inflammatory responses, and provide valuable information for NP design to achieve alleviated inflammation in biological systems.…”
Section: Introductionmentioning
confidence: 99%